Association of enlarged perivascular spaces with upper extremities and gait impairment: An observational, prospective cohort study - Hou, Yutong; Yang, Shuna; Li, Yue; Qin, Wei; Yang, Lei; Hu, Wenli (Frontiers in Neurology, 2022)
Background and objective Gait disturbances are common in the elderly and can lead to the loss of functional independence and even death. Enlarged perivascular space (EPVS) and motor performance may be related, but only few studies have explored this relationship. The aim of our study was to investigate the effects of both the severity and location of EPVS on movement disorders. Method Two hundred and six participants aged between 45 and 85 years old with complete magnetic resonance imaging (MRI) data were included in our analysis. EPVS were divided into basal ganglia (BG) and centrum semiovale (CSO), and their grades were measured. Gait was assessed quantitatively using a 4-m walkway and TUG test as well as semi-quantitatively using the Tinetti and SPPB tests. The function of upper extremities was evaluated by 10-repeat pronation–supination, 10-repeat finger-tapping, and 10-repeat opening and closing of the hands. Results Both high-grade EPVS, whether in BG and CSO, were independently correlated with gait parameters, the TUG time, Tinetti, and SPPB tests. The EPVS located in BG had a significant association with 10-repeat finger-tapping time (β = 0.231, P = 0.025) and a similar association was also observed between CSO-EPVS and 10-repeat pronation–supination time (β = 0.228, P = 0.014). Conclusion Our results indicated that EPVS was associated with gait disturbances, and a further investigation found that EPVS has an association with upper extremities disorder. EPVS should be considered as a potential target for delaying gait and upper extremities damage since CSVD can be prevented to some extent.